The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0894845312472254
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Career Success for Minority Researchers in the Behavioral Sciences

Abstract: The United States falls short in the diversity of its scientific workforce. While the underrepresentation of minority researchers in the behavioral sciences has been a concern for several decades, policy and training initiatives have been only marginally successful in increasing their number. Diversity plays a critical role in our nation’s capacity for research and innovation, yet current approaches prove inadequate. The current study used a qualitative approach to investigate the institutional, cultural, skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Women working in STEM fields acknowledged their struggle in simultaneously managing the demands at work and at home (Allen et al, ; Duberley & Cohen, ; Kameny et al, ). As a woman in STEM, one participant attributed her struggle to “being a very involved mother of two young kids and still wanting to be a 'rising star' at work”—the trajectory she had before marriage and family (Kameny et al, , p. 55). Work and family issues were identified as career barriers to women working in IT (Orser et al, ), with challenges including taking care of children and the elderly while dealing with the pressing demands of the job.…”
Section: Findings About Stem Women's Career Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Women working in STEM fields acknowledged their struggle in simultaneously managing the demands at work and at home (Allen et al, ; Duberley & Cohen, ; Kameny et al, ). As a woman in STEM, one participant attributed her struggle to “being a very involved mother of two young kids and still wanting to be a 'rising star' at work”—the trajectory she had before marriage and family (Kameny et al, , p. 55). Work and family issues were identified as career barriers to women working in IT (Orser et al, ), with challenges including taking care of children and the elderly while dealing with the pressing demands of the job.…”
Section: Findings About Stem Women's Career Experiencesmentioning
confidence: 99%
“…We were also able to identify institutional variables that either enabled or inhibited the STEM women's career progression, including gender discrimination and lack of career progression policies. The remaining ten studies did not mention any guiding theories (Aaltio & Huang, 2007;Duberley & Cohen, 2010;Ecklund, Lincoln, & Tansey, 2012;Glass, Sassler, Levitte, & Michelmore, 2013;Hatmaker, 2013;Kameny et al, 2014;Orser, Riding, & Stanley, 2012;San Miguel & Kim, 2015 Select Search Terms: • "women," "woman," "female," "gender", "science" "technology," "engineering," "math," or "STEM,", "career" or "career development", "job", "employment" or "vocation"…”
Section: Guiding Theoretical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant message of this study is to emphasize "situated" within the Situated Learning (Lave & Wenger, 1991), that "everyone can to some degree be considered a 'newcomer' to the future of a changing community" (p. 117) and can contribute to "the sustained character of developmental cycles of communities of practice" (p. 121). Kameny et al, (2014) identified four kinds of barriers to success for minority faculty researchers in the behavioral sciences: institutional, cultural, skills and personal. Institutional barriers include lack of mentors and support.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, feedback from the NHSN has indicated that these innovative career development activities are highly acceptable and feasible. While continued attention and funding are needed to promote effective and sustainable mentoring, networking, and career development for many groups of minority scientists (Kameny et al, 2014; Kosoko-Lasaki, Sonnino, & Voytko, 2006), we believe that this evidence-based and culturally relevant model holds great promise for other groups focused on increasing the representation of racial/ethnic minority scientists in health disparities research. Ultimately, more equitable representation of diverse communities across scientific disciplines will be critical to addressing substance use and health problems that disproportionately affect United States minority populations.…”
Section: Discussionmentioning
confidence: 99%